The influence of chemically treated natural fibers in poly (lactic acid) composites containing thymol - Mohamed Amin Tawakkal, Intan Syafinaz; J. Cran, Marlene; W. Bigger, Stephen (John Wiley & Sons, 2018)
The mechanical, thermal, and morphological properties of poly(lactic acid) (PLA) composites incorporated with 30% w/w untreated kenaf (UK) or treated kenaf (TK) fibers was explored together with the inclusion of 5%–10% w/w thymol for potential antimicrobial packaging material applications. The TK fiber composites had significantly higher tensile strength than those containing UK fibers. Scanning electron micrograph images showed a better adhesion between the TK fibers and the matrix was achieved resulting in improved reinforcement of the PLA/TK fiber composite. The neat PLA and composites containing 10% w/w thymol exhibited lower processing torque, tensile strength, and glass transition temperatures than those without thymol suggesting a possible lubricating and/or plasticizing effect. However, the incorporation of thymol into PLA at this level as well as into the composites did not influence the flexibility of the materials as a whole. Decomposition in compost progressed rapidly for neat PLA and PLA/thymol resulting in complete disintegration within 35 days. The presence of kenaf slightly inhibited the decomposition although complete disintegration of the composite was achieved within 48 days. The results suggest that PLA composites containing kenaf have the potential to be developed as rigid, compostable food packaging items such as trays from biodegradable and renewable resources.